Analisis Teologis Relasi Logika dan Iman Kristen - Laia, Sutarman; Sory, Putri; Lawalata, Mozes (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2024)
This research aims to explore the relationship between logic and Christian faith through a philosophical and theological approach. The research methods used include text and literature analysis, such as the Bible, articles and books. This research is motivated by the existence of a paradigm between logic and Christian faith which has been misunderstood so far. Starting from this problem, this research offers ideas that include an understanding of the significant relationship between logic and Christian faith. Although to certain limits there are dimensions of the divinity of the Christian faith that cannot be touched by logical thinking, such as the concept of the triune God, the end of time, and the divinity of God and His eternity. In principle, the only logic that can be compatible with the Christian faith is logic that has been born again. Therefore, it is important to recognize that the relationship between logic and Christian faith is not always contradictory, but can complement each other in strengthening human understanding of complex spiritual and intellectual principles. The relationship between logic and Christian faith is an interesting subject to study because it involves complex and profound aspects of human thought.